Microcontroller based ratio control for electro-mechanical dual acting pulley continuously variable transmissions - Aries Budianto, 1985- author; Kamarul Baharin Tawi, supervisor; Mohamed Hussein; Fakulti Kejuruteraan Mekanikal (2014)
Thesis (Sarjana Kejuruteraan (Mekanikal)) - Universiti Teknologi Malaysia, 2014